Algometer Assessment of Pressure Pain Threshold After Onabotulinumtoxin-A and Physical Therapy Treatments in Patients With Chronic Migraine: An Observational Study - Deodato, Manuela; Granato, Antonio; Ceschin, Marta; Galmonte, Alessandra; Manganotti, Paolo (Frontiers in Pain Research, 2022)
The purpose of this study is to evaluate pain hypersensitivity in chronic migraine patients three months from undergoing Onabotulinumtoxin-A therapy, physical therapy, or the combination of the two. Pressure Pain Threshold was assessed in accordance with Andersen’s guidelines, focusing on five muscles in the trigeminocervical area (namely trapezius, levator scapulae, temporalis, sub-occipitalis, and scalenus medius) and one muscle outside of the area, (i.e. tensor fasciae latae). Moreover, three headache parameters, namely attack frequency, duration and pain intensity, were recorded in an ad hoc diary kept by the patients. A total of 30 patients were included in three treatment groups: 1. Onabotulinumtoxin-A therapy, 2. physical therapy, and 3. Combination of Onabotulinumtoxin-A and physical therapy. The results show that, at the final assessment, the Pressure Pain Threshold was significantly reduced in the combined treatment group compared to the two single-therapy groups. As regards headache parameters, frequency and duration of the attacks decreased significantly in all three treatment groups, whereas pain intensity reduction was statistically more significant in the combined treatment group compared to group 1 and 2. Results suggest that a better pain modulation in patients with chronic migraine can be achieved with a combined treatment of Onabotulinumtoxin-A and physical therapy. Indeed, the combination of both pharmacological and non-pharmacological treatments results in reduction of both headache-related parameters, and widespread pressure hyperalgesia.